Catalytic Pyrolysis of Palm Oil Decanter Cake using CaO and γ-Al2O3 in Vacuum Fixed Bed Reactor to Produce Bio-oil - Nugroho, Dewayanto; Ruzinah, Isha; Mohd Ridzuan, Nordin (2013)
The objective of this paper is to present the influence of catalyst towards the properties of bio-oil produced from Palm oil decanter cake (PDC), a semi-solid waste from palm oil milling plant. The PDC was first dried in oven at 105 °C for 24 hours to remove moisture and then ground to particle size of 0.85 – 2 mm. The dried PDC was then pyrolysed under dynamic vacuum at 500 °C, with temperature increased at 15 °C/min and maintained at the final temperature until no more product were formed. Two catalysts, the basic CaO and acidic γ-Al2O3 were used. The catalyst was mixed with decanter cake at various sample to catalyst weight ratio to investigate the effect of catalyst amount towards bio-oil production. In-terms of bio-oil yield and its HHV value, CaO performed better than γ-Al2O3. It is also found that 5 wt% of calcium oxide to sample produced the highest yield on bio-oil production. The oil was also characterized using 1H-NMR, FTIR, CHNS analyzer and GC-MS. The analyses show that bio-oil obtained through catalytic pyrolysis of PDC is slightly different from that produced via non-catalytic process. GC/MS data indicates that the addition of calcium oxide reduced the content of carboxylic acid in bio-oil significantly. In addition, the bio oil produced from PDC has near neutral acidity , with pH value of 6.38, 6 and 8 for non catalytic, γ-Al2O3 and CaO catalytic pyrolysis, respectively. It can be deduced from this study that CaO can be used to enhance the production of bio-oil from decanter cake.